A tungsten nitride-based degradable nanoplatform for dual-modal image-guided combinatorial chemo-photothermal therapy of tumors. Issue 4 (15th January 2019) - Zhang, Cheng; Wang, Shi-Bo; Chen, Zhao-Xia; Fan, Jin-Xuan; Zhong, Zhen-Lin; Zhang, Xian-Zheng
Abstract : A tungsten nitride-based multifunctional nanoplatform is developed for tumor theranostic applications, which shows the great potential of tungsten nitride nanoparticles in the biomedical field. Abstract : An innovative tungsten-based multifunctional nanoplatform composed of polyethylene glycol (PEG)-modified tungsten nitride nanoparticles (WN NPs) is constructed for tumor treatment. The PEG-WN NPs not only possess strong near-infrared (NIR) absorbance, high photothermal conversion efficiency, and excellent photothermal stability, but also effectively inhibit tumor cells upon 808 nm laser irradiation. After coating with thiolated (2-hydroxypropyl)-β-cyclodextrin (MUA-CD) on the surface, such a nanoplatform can also be used for drug delivery (such as DOX) and presents a synergistic tumor inhibition effect both in vitro and in vivo . Furthermore, the PEG-WN NPs present good contrasting capability for X-ray computed tomography (CT) and photoacoustic (PA) imaging. With PA/CT imaging, the tumor can be accurately positioned for precise treatment. It is worth mentioning that PEG-WN NPs are biodegradable and could be effectively excreted from the body with no appreciable toxicity in vivo . It is expected that this biocompatible multifunctional nanoplatform can serve as a potential candidate for tumor treatment in future clinical applications.